Shielding Processing Technique through the Calculations and Measurements of the Time Averaged Cross-Section of Multiphase Domain (Global Journals of Research in Engineering, 2012)
The dual source computed tomography (DSCT) setup has been developing in the central and has potential for use as anon-invasive tool for determining the time averaged cross section of multiphase domain. The two sources used in (DSCT) setup are located inside source collimator device (SCD) to collimate the beam to give it a fan shape. The count rate of un-attenuated photons will be measured by two sets of detectors. Radiation shielding is based on the principle of attenuation, which is the ability to reduce a wave#x2019;s or ray#x2019;s effect by blocking or bouncing particles through a barrier material. Charged particles may be attenuated by losing energy to reactions with electrons in the barrier, while gamma radiation is attenuated through scattering, or pair production. . Calculated results showed a substantial convergence with the real measurement values of dose rates especially in the common points.
Keywords: Shielding; Arrays; Scanning; Dose rate; Time averaged